Modern methods of irrigation water purification by a mesh-filter using influence of low frequency vibration - Bilokon, S.; Turbal, Y.; Kunanets, N.; Pasichnyk, V. (My University, 2019)
The article is devoted to the analysis of different methods of irrigation water purification from suspended particles. There have been considered the problems of irrigation water purification by using the low-frequency vibration technology and the effects arising from the influence of vibration on the water with different floating impurities. Vibration parameters that allow obtaining the effect of standing wave was substantiated. Also in the article have been disclosed the influence of low-frequency vibration on the quality of water purification depending on the types of pollution and their granulometric composition. Obtained the hydraulic characteristics of the mesh such as the effect of vibration on the pressure loss.
Keywords: irrigation water; low-frequency vibration; standing wave; floating impurities